The role of quality aspects for the adequacy of business processes and business information systems. (11th August 2009) - Adam, Sebastian; Riegel, Norman; Doerr, Joerg
In the requirements engineering area, it has been recognised that quality issues are essential for the success of any system development and that they should be considered right from the beginning of every project. Even though quality also plays a central role in business process management, systematic consideration of quality requirements is still missing. In this article, we therefore discuss that the continuous traceability of quality might lead to more adequate business processes and supporting information systems. To underpin this position, we develop – based on our many years of experience in the information systems domain – a meta-model, mathematical dependencies and a development method that show how quality goals, business processes and quality requirements for the involved systems are intertwined and how they influence each other.